DIGITAL TRANSFORMATION IN EDUCATIONAL MANAGEMENT: CHALLENGES AND OPPORTUNITIES - Mokhira Akromova Akmal qizi; Mamarajabov Shavkat Ergashevich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation: This thesis explores the impact of digital transformation on educational management, emphasizing the challenges and opportunities that emerge as schools and universities integrate advanced technologies into their operations. It analyzes recent global research and theoretical frameworks concerning digital leadership, data-driven decision-making, and institutional change. The study identifies key challenges such as digital inequity, insufficient managerial capacity, data governance, and resistance to change. At the same time, it highlights major opportunities, including improved administrative efficiency, personalized learning systems, and enhanced collaboration through digital tools. The thesis concludes that successful digital transformation in educational management requires visionary leadership, ethical governance, continuous professional development, and equitable access to technology. The findings contribute to the broader understanding of how digital innovation can be effectively managed to promote sustainable, inclusive, and high-quality education in the 21st century.